Fetal mortality and the challenges for women's health care in Brazil - Patrícia de Sá Barros; Érika Carvalho de Aquino; Marta Rovery de Souza (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To establish a historical series of fetal mortality in Brazil and regions between 1996 and 2015, identifying its behavior and trend. METHODS: A descriptive study on cases of fetal deaths in Brazil and in each region reported from 1996 to 2015, registered in DATASUS and classified by ICD-10. Maternal age and schooling, duration of gestation and type of delivery were considered. We calculated the fetal mortality rate between 1996 and 2015 to build historical series. RESULTS: The time series shows a steady chart of the fetal mortality rate (FMR) from 2000 in Brazil and in all regions. The country's fetal mortality rate rose from 8.19 in 1996 to 9.50 per 1,000 births in 2015. There was an increasing trend in fetal deaths whose root cause appears in chapter XVII of ICD-10 in Brazil and in all regions. Deaths from Chapter XVI causes showed a trend of increase only in the Northeast region, while other basic causes showed a trend of increase in the Southeast and South regions. In the Brazilian scope, there was an increasing trend of fetal deaths in mothers in the 10-14 and 25-44 years age groups. In Brazil and in all regions, there was an increase of the FMR in women with more than 8 years of schooling. Fetal deaths predominated between 28 and 36 weeks of gestation, with a growing trend in Brazil and all regions, except in the South (steady). Vaginal delivery prevailed, with a steady trend, while cesarean sections showed an increasing trend in Brazil and in all regions. CONCLUSIONS: The quality of information about fetal deaths, investments in research committees, and improvement in the quality of prenatal care should be prioritized to enable more effective coping and to reduce the fetal mortality rate in Brazil.